Chatbot para apoio a consulta de enfermagem à gestante em investigação para toxoplasmose e às infectadas - Zamboni, Rafaela Cassiano (2024)
Introduction: Toxoplasmosis is a disease that affects a significant number of pregnant women, whose infection can occur at any stage of conception. Maternal involvement can cause complications to the fetus, therefore, it is essential that nurses act in capturing infected pregnant women in the investigative process carried out during prenatal care, requiring professionals to perform interventions based on multifactorial assistance, with a view to an immediate approach, anchored in use of technologies that enable teaching on the subject and guaranteeing the patient a safe pregnancy. Objective: Develop and evaluate a conversational technology to assist nurses in tracking toxoplasmosis in pregnant women and monitoring those infected. Method: This is applied technological development research. This study will be developed in three stages. In the first stage, the content was developed through documentary research by surveying the main needs related to pregnant women with toxoplasmosis. In the second stage, the script was developed, the platform was chosen, the chatbot conversational design and the development of educational technology were developed. In the third stage, the usability assessment of the technology will be carried out using the System Usability Scale (SUS) applied to nurses who will participate in the research. Product: Guiding conversational technology to assist in tracking toxoplasmosis in pregnant women and treating those infected. Result/Product: The tool was developed to assist nurses in tracking toxoplasmosis in pregnant women and monitoring those infected. The tool has synthesized information to cover the actions recommended by the Ministry of Health in less time and making teaching viable. The Toxobot application is unprecedented and serves as support for the execution of prenatal activities, advising the Primary Care nurse in clinical reasoning and in making diagnostic decisions in an assertive manner. Conclusion: the study made it possible to create a tool to support teaching learning with adequate and synthesized information for tracking toxoplasmosis in pregnant women and monitoring those infected, constituting a disease surveillance strategy and allowing the necessary interventions, having potential for organizing the work process of PHC nurses, being a relevant product for scientific and technological development, with the potential to generate impact and be applied at a local, regional and national level, as they can be used by other professionals and health services when carrying out pre-service -Christmas. The technology is a demand from the municipality of Vila Velha that was validated with the Primary Care nurses